Grammatical Error Analysis in Essay Writing - Rifa Suci Wulandari; Ratri Harida (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
Students cannot avoid making errors which might enrich learners’ knowledge in using a foreign language. Error as such a systematic deviation which occurs when the student has not learned something of the language and gets it wrong constantly, because he has not learned the correct form. However, there are some factors that cause the errors such as carelessness, first language interference, and translation. When using English in their essays writing, students might make errors in various aspects of grammar, such as tenses, aspects, word classes, word order, inflections, and punctuation. Therefore, the accuracy of using them in the writing of English sentences must be considered, especially by students who are developing writing skills in English as a foreign language. By writing English sentences according to the grammatical structure, the meaning of it will be accurate, easily understood and acceptable. This article aims to identify types of grammatical errors made by the students of English education department at STKIP PGRI Ponorogo in writing essay and find out the factors causing the students’ grammatical errors in writing essay.